Treatment patterns and outcomes in early-stage ALK-rearranged non-small cell lung cancer. (April 2022) - Schmid, Sabine; Garcia, Miguel; Cheng, Sierra; Zhan, Luna; Chotai, Simren; Balaratnam, Karmugi; Khan, Khaleeq; Patel, Devalben; Catherine Brown, M.; Sachdeva, Robin; Xu, Wei; Shepherd, Frances A.; et al.
Highlights: Treatment in patients with ALK + early stage disease is similar to unselected patients. Durvalumab appears safe in patients with unresectable stage III ALK + disease. Degree of benefit of durvalumab in unresectable stage III ALK + disease remains unclear. Abstract: Introduction: We evaluated the baseline demographics, treatment patterns, and outcomes of patients with ALK-rearranged early stage (Stage I-III) non-small cell lung cancer (NSCLC). We also evaluated the efficacy and toxicity of durvalumab consolidation treatment in patients with ALK-rearranged unresectable stage III disease. Methods: Retrospective chart-review analysis of all patients with histologically confirmed stage I-III reflexively tested ALK-rearranged NSCLC managed with curative intent at two Canadian Centers. Results: Of 48 patients, 19 (40%) were stage I, 5 (10%) were stage II and 24 (50%) were stage-III. Median progression-free survival (PFS) was 27.6 months overall (95%CI: 20.5–51.4) and 144.4 months in stage-I, 27.6 months in stage-II and 14.9 months in stage III patients. Of 20 patients with unresectable stage-III disease treated with chemoradiation (9 also received durvalumab consolidation), 18/90% have relapsed. Median PFS was 10.9 months (95%CI:5.9–22.5). A non-significant trend toward improved PFS was seen in patients receiving additional durvalumab compared to patients treated with chemoradiation alone (median PFS, 12.5 vs 5.9 months, p = 0.16). Toxicity-related treatment modifications on subsequent first ALK-TKI at time of metastatic disease were needed in three (33%) patients who had received chemoradiation alone and two (29%) patients with consolidation durvalumab; no relevant pulmonary or hepato-toxicity was observed overall. Conclusion: Treatment strategies and PFS of patients with Stage I-III ALK-rearranged NSCLC are similar to patients without molecular driver alterations. Durvalumab consolidation treatment appears generally safe in patients with unresectable stage III ALK-rearranged disease; however, the degree of benefit of such an approach remains unclear.